Auditoría Financiera y su relación con las compras públicas en la administración eficiente de la Municipalidad Distrital de Belén, periodo 2023 – 2024 - Diaz Ruiz, Jack Juseph (2025)
In this research, the relationship between Financial Audit and public procurement in the efficient administration of the District Municipality of Belén was studied during the period 2023-2024. The study was descriptive quantitative, with a non-experimental, cross-sectional, and retrospective design. The Questionnaire and the Registration Form were used as instruments, and a documentary analysis or review of the statistical information obtained from the Electronic State Procurement System (SEACE-OSCE) and the Ministry of Economy and Finance (MEF) was carried out. A positive perception was identified among the surveyed population, 66 civil servants and officials, where the significance value is less than 0.050, and Spearman's Rho was used, obtaining a moderate positive correlation (0.462) between the Financial Audit with the Annual Procurement Plan, with the selection processes, and with the transfer of income and the execution of payments, for efficient programming and management of spending in the contracting of goods, services and non-financial assets. During the years 2023 and 2024, its main financing was the Determined Resources, and the primary attention of the obligations in different products and goals was in current expenses (goods and services, personnel, social obligations and pensions), with less attention being paid to Non-Financial Asset.